Full Time School: Policy, Curriculum and Pedagogic Challenges - Sandra Valéria Limonta (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
This article discusses the design of a full-time school that is under construction in our country, articulating policy, history and a theoretical reflection on the curriculum organization and pedagogical work in full-time schools. From literature review and as a research procedure for an investigation of curriculum and teaching in public full-time school, we theoretically problematize two concepts that can contribute to the debate: integrated curriculum and pedagogical mediation.